THE INFLUENCE OF E-CATALOG SYSTEM QUALITY, HUMAN RESOURCE COMPETENCE, AND FACILITIES ON IMPROVING THE QUALITY OF GOODS AND SERVICES PROCUREMENT IN THE BATAM CITY GOVERNMENT - Ayu Silvia Dewi; Suyono; Mulyadi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2026)
With a focus on the Batam City Government's e-Catalog system quality, human resource competency, and supporting facilities, this study investigates the elements that affect the quality of procurement services in the context of digital public procurement. 93 respondents who were familiar with the e-Catalog system personally took part in a structured survey that collected data using a quantitative explanatory method. The data was assessed using multiple linear regression to examine both partial and simultaneous effects between factors. The findings indicate that while e-Catalog system quality has a positive but statistically insignificant impact, human resource competency has a negative and negligible connection with procurement service quality. Conversely, facilities have a positive and statistically significant influence on service quality and are the most significant factor. With a coefficient of determination of 62.3%, all independent variables simultaneously strongly contribute to the quality of procurement services, demonstrating the model's strong explanatory power. These findings imply that infrastructural preparedness is more important than system complexity or human resource capacity when it comes to local government digital procurement. By emphasizing the significance of matching technology systems with suitable facilities to improve service performance, this study adds to the body of knowledge in public administration. Policymakers should emphasize infrastructure development while continually enhancing system quality and human resource competency, according to the findings.